A STUDY ON PRICE BEHAVIOUR OF IMPORTANT VEGETABLES IN HYDERABAD - D. SRINIVASA CHARY, S.T. PRADEEP KUMAR , T. LAVANYA, K. SUHASINI and (The Journal of Research, PJTSAU, 2020)
Agriculture plays a vital role in Indian economy. India is the second largest producer of vegetables, next to China with annual production of 184 milliontonnes in the year 2017-18 accounting for nearly 12 percent of world production of vegetables.Uttar Pradesh and West Bengal are the largest vegetable producing states in India with annual production of nearly 29 and 28 million tonnes accounting for 15.4 and 15.04 percent of total vegetables production respectively. Telangana state accounts for only 1.4 percent of total vegetables production in india with annual production of 2.7 million tonnes in 2017-18.